Performance Evaluation of Nipa-Nipa Sludge Treatment Plant in Makassar - Nita Arina Fahmi; Eddy Setiadi Soedjono (International Journal of Social Service and Research, 2022)
The purpose of this study is to evaluate the processing units at Nipa-Nipa Sludge Management Installation (IPLT) on technical aspect to find out which units need improvement, economic feasibility of the current IPLT and the economic feasibility if improvements are made, and evaluate the institution that manages IPLT so that it can maximize IPLT operation and maintenance. The method used to evaluate the technical aspects is a comparison between the design criteria of planning and the design of existing criteria. The results of the evaluation of the technical aspects indicate the existing IPLT processing unit can still be operated and able to reduce contaminant levels to below the quality standard with improvements to several processing units without additional units. Furthermore, for the economic aspect, it shows the economic feasibility of this IPLT will recover with the addition of the number of customers by 17% of the number of existing customers each year. Meanwhile, for the institutional aspect, there are opportunities for institutional development from the Service Technical Implementation Unit (UPTD) institutional form to an institutional form with the Financial Management Pattern of the Regional Public Service Agency (PPK-BLUD). As for the results of this research, it can be implemented as a consideration for the Makassar City Government in making decisions to carry out IPLT rehabilitation and planning. Besides that, it also provides strategic recommendations and solutions to existing financial problems to the Makassar City UPTD PAL in institutional management, especially in the development of the UPTD PAL itself.